Generation Z’s Approach to Searching for and Performing Work - Nowak, Dariusz; Nikolov, Emil; Wiśniewska, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The main purpose of the article is to identify the most significant factors influencing Generation Z’s approach to work. The priorities that guide individuals of this generation in looking for and performing work were established and then assessed. Research Design & Methods: The paper conducts a critical review of the literature before presenting quantitative research. The basis for the empirical research was a two-part questionnaire. The first one was a data sheet used to characterise the sample, while the second contained closed questions that respondents rated on a 5-point Likert scale. The collected empirical material was coded and converted into numerical data for detailed analyses of the population. The scale enabled us to determine the strength and direction of the impact of each variable. Due to the multidimensional and multifaceted nature of the problem, factor analysis procedures were used. The decisive factor for choosing this procedure was the individualised and subjective nature of most responses. Calculations were done with Statistica StatSoft 13.3, using descriptive statistics, correlations, and multivariate analyses. The survey was conducted in late 2022 and early 2023 on a sample of 428 representatives of Generation Z. Findings: The results showed that Generation Z’s approach to work is pragmatic and confrontational. In their search for and performance of a job, they consider standard factors such as: salary adequate to the commitment and the position, various employee benefits, and the relationship and atmosphere in the workplace. At the same time, they strive for independence, prefer flexible working hours, seek understanding, forbearance and empathy and, above all, lack of exploitation and being overloaded with tasks. Implications / Recommendations: Demographic changes in today’s world have forced companies to change their employment policies. In many cases, the methods have not met expectations, which has been a factor in the widening employment gap. Our research could help entrepreneurs understand Generation Z and fashion job offers that are attractive to Gen Z as it enters the labour market. They should also help Gen Z navigate the labour market, particularly regarding employer expectations and conditions. Contribution: The results of the study are a voice in the discussion on the behaviour, expectations, approach and commitment of Generation Z in the labour market. The factors confirm other research and underscore the dynamic changes this generation is exhibiting as it carves out its place in socio-economic life.